2016
DOI: 10.1108/jsm-12-2014-0409
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of customer price sensitivity: an empirical analysis

Abstract: Purpose Consumer price sensitivity has become a major issue over the past few decades. This paper aims to investigate the importance that insurance customers give to premiums, insurers, intermediary recommendations and bundling strategies. The relationship between attributes and consumer price sensitivity is also studied. Design/methodology/approach To calculate the importance of attributes and part-worth utilities, a Conjoint Analysis with Full Profile was performed. To segment the market, a two-stage clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 74 publications
2
30
0
3
Order By: Relevance
“…A study conducted by (Dominique-Ferreira, S., Vasconcelos, H., & Proença, 2016) reported that pricing has also been debated over the past few decades because it is difficult to estimate and has also influenced business profit. Therefore, the challenge of setting the right price often means that not all consumers are willing to pay for a given item at a comparable value.…”
Section: Product Pricementioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by (Dominique-Ferreira, S., Vasconcelos, H., & Proença, 2016) reported that pricing has also been debated over the past few decades because it is difficult to estimate and has also influenced business profit. Therefore, the challenge of setting the right price often means that not all consumers are willing to pay for a given item at a comparable value.…”
Section: Product Pricementioning
confidence: 99%
“…Therefore, the challenge of setting the right price often means that not all consumers are willing to pay for a given item at a comparable value. (Dominique-Ferreira, S., Vasconcelos, H., & Proença, 2016) have noted that the company's overall revenues and market acceptance were taken into account in the pricing strategies. The chances of success in achieving the corporate profitability goal will be higher if managers have more information and well-equipped with the reactions of consumers over the price.…”
Section: Product Pricementioning
confidence: 99%
“…So that the bundling strategy is considered ineffective and triggers consumer dissatisfaction. Bundling with a variety of products that can provide new benefits can also reduce the risk of unfairness (Dominique-Ferreira et al, 2016; 2017) [13][12], because it makes consumers reluctant to compare with others. Likewise the application of dynamic prices must be adjusted to time, consumers, and / or circumstances based on consumer characteristics (Haws & Bearden, 2006) [22].…”
Section: Dynamic Bundling and Dynamic Pricing On Satisfactionmentioning
confidence: 99%
“…Variable of dynamic pricing is measured using three questions(Petro, 2015)[34]. Dynamic bundling variables with three items of questions (Dominique-Ferreira et al, 2016[13];Li et al, 2018).…”
mentioning
confidence: 99%
“…() utilized discrete choice data to investigate whether price framing affects choice in mixed‐price bundles, and found that the joint and integrated frame results in the highest proportion of respondents choosing the bundle and the fewest choosing “none.” Dominique‐Ferreira et al. () investigated the importance that insurance customers give to premiums, insurers, intermediary recommendations, and bundling strategies, and studied the relationship between attributes and consumer price sensitivity.…”
Section: Introductionmentioning
confidence: 99%